Simple Versus Complex Preoperative Carbohydrate Drink to Preserve Perioperative Insulin Sensitivity in Laparoscopic Colectomy: A Randomized Controlled Trial. Issue 5 (May 2020) - Karimian, Negar; Kaneva, Pepa; Donatelli, Francesco; Stein, Barry; Liberman, A. Sender; Charlebois, Patrick; Lee, Lawrence; Fiore, Julio F.; Carli, Francesco; Feldman, Liane S.
Abstract : Supplemental Digital Content is available in the text